Magnetically mediated thermoacoustic imaging - Feng, Xiaohua (2014)
In this paper, alternating magnetic field is explored for inducing thermoacoustic effect on dielectric objects. Termed as magnetically mediated thermo-acoustic (MMTA) effect that provides a contrast in conductivity, this approach employs magnetic resonance for delivering energy to a desired location by applying a large transient current at radio frequency below 50MHz to a compact magnetically resonant coil. The alternating magnetic field induces large electric field inside conductive objects, which then undergoes joule heating and emanates acoustic signal thermo-elastically. The magnetic mediation approach with low radio frequency can potentially provide deeper penetration than microwave radiation due to the non-magnetic nature of human body and therefore extend thermoacoustic imaging to deep laid organs. Both incoherent time domain method that applies a pulsed radio frequency current and coherent frequency domain approach that employs a linear chirp signal to modulate the envelop of the current are discussed. Owing to the coherent processing nature, the latter approach is capable of achieving much better signal to noise ratio and therefore potential for portable imaging system. Phantom experiments are carried out to demonstrate the signal generation together with some preliminary imaging results. Ex-vivo tissue studies are also investigated.